BOOK REVIEW OF BATTLE HYMN OF THE TIGER MOTHER WRITTEN BY AMY CHUA - Monica, Martha (LANTERN (Journal on English Language, Culture and Literature), 2016)
This project analyses a novel by Amy Chua entitled Battle Hymn of the Tiger Mother. The aims of the project are to make a summary of the novel by exposing the difference between Chinese and American parenting system and revealing the implicit opinions of the society in the novel about the Chinese and American parenting system. The method that underlies this project is cultural heritage method by Helaine Ruggles, D Fairchild The methods used in this study are library research and. The analysis shows that in this novel the writer represents the Chinese parents with Chinese parenting system and compares with the American parenting systemthat later creates society’s opinion.